Responsabilidad patrimonial del Estado por privación injusta de la libertad frente a los criterios jurisprudenciales (2016)
The liability of the state for wrongful deprivation of liberty seemed to us a very interesting for our research topic, covering issues of great importance to the legal learning, it should be noted that this issue is elevated to constitutional status and is established in article 90 of the charter, is established primarily the responsibility of the State to generate serious consequences to citizens who for some reason are deprived of liberty but during the process can prove they are innocent, in which case the State must enter the damages of a patrimonial way either by action or omission of its state agents. Freedom is one of the most precious rights that human beings have, and being breached abruptly this must be compensated for the offenses they commit against it, in this case the state must take responsibility and face the legal consequences situcion this entails.